2010
DOI: 10.1016/j.socscimed.2010.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Allostatic load is associated with chronic conditions in the Boston Puerto Rican Health Study

Abstract: Puerto Ricans living in the United States mainland present multiple disparities in prevalence of chronic diseases, relative to other racial and ethnic groups. Allostatic load (AL), or the cumulative wear and tear of physiological responses to stressors such as major life events, social and environmental burden, has been proposed as a possible mechanism for the inequalities observed in minority groups, but has not been studied in Puerto Ricans. The aim of this study was to determine the association of AL to six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
165
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(170 citation statements)
references
References 64 publications
3
165
0
2
Order By: Relevance
“…In other research, medications were accounted for by adjusting the construction of the reported ALI. For example, some researchers add a point for every biomarker directly affected by a medication to the ALI regardless of the biomarker's current level, although specific adjustments vary by study (Ar evalo, Tucker, & Falc on, 2014;Doamekpor & Dinwiddie, 2015;Gale, Booth, Starr, & Deary, 2015;Hampson et al, 2009;Mattei et al, 2010;Robertson et al, 2014;Robertson & Watts, 2016 Clinically based constructs directly counteract the usefulness of ALIs to determine individuals in a group at greatest underlying risk for future health issues and early mortality. However, within medical settings, applying ALIs using clinical cut-points may be more practical, particularly as sample distributions are not usually available when working with individual patients (Mauss et al, 2016).…”
Section: Methods Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In other research, medications were accounted for by adjusting the construction of the reported ALI. For example, some researchers add a point for every biomarker directly affected by a medication to the ALI regardless of the biomarker's current level, although specific adjustments vary by study (Ar evalo, Tucker, & Falc on, 2014;Doamekpor & Dinwiddie, 2015;Gale, Booth, Starr, & Deary, 2015;Hampson et al, 2009;Mattei et al, 2010;Robertson et al, 2014;Robertson & Watts, 2016 Clinically based constructs directly counteract the usefulness of ALIs to determine individuals in a group at greatest underlying risk for future health issues and early mortality. However, within medical settings, applying ALIs using clinical cut-points may be more practical, particularly as sample distributions are not usually available when working with individual patients (Mauss et al, 2016).…”
Section: Methods Studiesmentioning
confidence: 99%
“…In general, higher allostatic load is associated with poorer physical performance and increased risk for physical decline (Seeman et al, 1997). Across research settings, higher allostatic load also is associated significantly with cardiovascular diseases (CVD; Karlamangla et al, 2002;Mattei et al, 2010;Seeman et al, 2002), abdominal obesity (Mattei et al, 2010), hypertension (Mattei et al, 2010), diabetes (Mattei et al, 2010), and arthritis (Mattei et al, 2010).…”
Section: Methods Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Prior research has shown higher AL to be associated with mortality, cardiovascular disease, and decreased physical and cognitive functioning. 8,9,[15][16][17][18][19] The formulation of AL by McEwen and Seeman 13 and Seeman et al 10 included primary mediators and secondary markers involved in physiological stress responses. Primary mediators are circulating hormonal agents that mediate the body's response to stressors through their effects on tissues and organs (e.g., cortisol, epinephrine, C-reactive protein [CRP] and dehydroepiandrosterone-sulfate [DHEA-S]).…”
Section: Introductionmentioning
confidence: 99%
“…Allostatic load is frequently quantified by measuring a range of biomarkers (e.g., blood pressure, cortisol, catecholamines, glycated hemoglobin, waist circumference, cholesterol, inflammatory markers), and allocating individuals scores based on the number of variables on which values are elevated compared with the sample distribution (9,10). Studies relating allostatic load measures with type 2 diabetes have been inconsistent to date (11,12). However, another aspect of allostasis is that it is manifest in modifications of dynamic responses to challenge, not only in basal measures.…”
mentioning
confidence: 99%